Hidrocefalia em Bulldog Francês - Nascimento, Victor Henrique Pinheiro do (Universidade Federal do Tocantins, 2023)
Hydrocephalus is a very common disorder in veterinary medicine. Can be classified as congenital or acquired and consists in the accumulation of cerebrospinal fluid (CSF), which leads to an increase of the ventricular system. The diagnosis is made with clinical examination and image. The treatment is only palliative, and may be surgical and lumefantrine. In this report is described and discussed a case of congenital hydrocephalus. The case was joined during supervised internship mandatory, held at SHUT-Animal Surgery and Specialized Diagnostic Laboratory in the city of Jundiaí-SP, in the period from 16 May to 22 July 2016.